2017
DOI: 10.1177/1010428317711655
|View full text |Cite
|
Sign up to set email alerts
|

High expressions of BCL6 and Lewis y antigen are correlated with high tumor burden and poor prognosis in epithelial ovarian cancer

Abstract: Aberrant regulation of BCL6 plays crucial oncogenic roles in various malignant tumors; howbeit, the function of BCL6 in tumorigenesis of ovarian cancer remains unclear. The aim of this study is to investigate the role of BCL6 in ovarian cancer. The methods of immunohistochemical staining, quantitative real-time polymerase chain reaction, immunocytochemical staining, and gene expression profile enrichment analysis were performed to identify the possible role of BCL6 in ovarian cancer. We observed that the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
(90 reference statements)
2
15
0
Order By: Relevance
“…B-cell lymphoma 6 (BCL6), also known as BCL6A, LAZ3, or ZNF51, belonging to the BTB-POZ protein family, has been demonstrated to facilitate cell proliferation [17]. Reports showed that BCL6 may be a novel diagnostic and treatment strategy for breast or ovarian cancer [27,28]. However, the role BCL6 plays in CRC remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…B-cell lymphoma 6 (BCL6), also known as BCL6A, LAZ3, or ZNF51, belonging to the BTB-POZ protein family, has been demonstrated to facilitate cell proliferation [17]. Reports showed that BCL6 may be a novel diagnostic and treatment strategy for breast or ovarian cancer [27,28]. However, the role BCL6 plays in CRC remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, BCL6 promoted glioma and served as a therapeutic target ( 26 ). high Lewis y antigen and BCL6 expressions in epithelial ovarian cancer were associated with poor prognosis and high tumor burden ( 27 ). BCL6 was increased and downregulated by miR-544 in triple-negative breast cancer to suppress tumor growth ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since lncRNAs could either repress (20) or prompt (21) the ubiquitination of target substrates, it is unclear whether the molecular mechanisms of LINC00152 in EOC are linked to the ubiquitination of downstream proteins. B-cell CLL/lymphoma 6 (BCL6) is a highly conserved zinc finger transcriptional factor and is implicated in the pathogenesis of human B-cell lymphomas by controlling the transcription of oncogenes (22). Previous studies demonstrate that BCL6 is degraded via the ubiquitin-proteosome system (23,24) and its degradation is balanced by FBXO11 (23) and AIP (25) thus regulating the tumor growth of diffuse large B cell lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrate that BCL6 is degraded via the ubiquitin-proteosome system (23,24) and its degradation is balanced by FBXO11 (23) and AIP (25) thus regulating the tumor growth of diffuse large B cell lymphoma. Recently BCL6 has also been reported to be dysregulated in somatic malignancies such as breast carcinoma (26,27) and EOC (22,28). However, it remains unclear whether degradation of BCL6 is related to lncRNAs and how the interaction is implicated in the tumorigenesis of somatic malignancies.…”
Section: Introductionmentioning
confidence: 99%